Conceptual Meaning of Secretary in Academic Students of Secretary’s Cognition in Bandung - Elvi Citraresmana (Universitas Teknokrat Indonesia, 2020)
This article discusses the conceptual meaning of secretary through the cognition of Academic Students of Secretary in Bandung. This research was conducted in order to find out how did the secretary students describe the meaning of “secretary” through their essay writing. This research is statistic descriptive analysis, data were collected through Antconc software in order to observe the frequentative words used by the students. The node words of this research is the word secretary in which this word is used as much as 408 times by the students. Through the Cluster/N-grams, it is observed that the students tried their best efforts to describe the secretary. The theory of Semantic Cognitive especially frame semantics and image schemas proposed by Lakoff (1987); Johnson (1987); Lakoff and Turner (1989); Clausner and Croft (1999); Fillmore (1985) are used to analyze the conceptual meaning revealed from the students’s essay writing. The understanding of statistic descriptive refers to Palmer study (1933). The results show that the students mapped the secretary as the container in which it needs the container. The results can be seen through frame semantics that secretary is brain, secretary is the heart, secretary is one’s hand, secretary is one’s face, and secretary is a foundation of building.